"An Asymmetric Doubling": A Nonstate Actor Using the Method of Doubling Sources—Hamas against Israeli Intelligence. Issue 1 (2nd January 2023) - Flamer, Netanel
Abstract: As part of its intelligence warfare against Israel, Hamas made the identification and targeting of collaborators with Israel a top priority. During those years, the Hamas practice was to apply different degrees of detention and torture of those suspected of collaborating. However, in some cases, Hamas chose a different tactic of exploiting collaborators to transform a threat into an opportunity. Hamas turned some collaborators into double agents, using them to advance its objectives. This article examines some of the doubling operations carried out by Hamas on Israeli collaborators over the last three decades. Examining these cases reveal how Hamas's doubling methods developed over time, concurrently with the movement's evolution. Thus, the doubling operations became more organized and sophisticated, being used for propaganda and deterrence purposes as well as other goals. The article explores an interesting aspect of Hamas's counterintelligence activity in its struggle against the state of Israel. In addition, it sheds light on how a nonstate organization can use doubling of sources as part of its asymmetric war against a state.